Tunable polaron-induced coloration of tungsten oxide: Via a multi-step control of the physicochemical property for the detection of gaseous F - Lee, Sang Yeon; Shim, Gowoon; Park, Jucheol; Seo, Hyungtak (Physical Chemistry Chemical Physics, 2018)
The tunable polaron effect of amorphous tungsten oxide on FTO substrates has been used to detect fluorine in the gas phase via photochemical and gasochromic reactions. By combining photochemical (UV exposure under an H2 atomsphere) and gasochromic (XeF2 exposure) reactions, the detection of gaseous fluorine using amorphous tungsten oxide is described. The effective hydrogenation of WO3 was achieved using UV/H2 exposure to prepare hydrogenated tungsten oxide (H-WO3-x) upon activating the strong polaron-coupling to infrared (IR) light to decrease IR transmission from 70 to 20% at 1000 nm wavelength. This is explained by creation of W 5d unpaired electrons excited by band-edge defect states or W5+ states. The H-WO3-x lattice structure was maintained as an amorphous structure and found to have hydrogen-associated shallow- and oxygen vacancy-associated deep-trap levels with a moderate enhancement of the n-type characteristic. The gasochromic reaction takes place within tens of seconds at room temperature upon exposure to XeF2 gas leading to atomic F insertion. Fluorine, which is one of the most electronegative materials, is combined with the W5+ and W6+ in H-WO3-x to remove H to form volatile HF vapor and the formation of W-F bonds. The global incorporation of fluorine effectively turns H-WO3-x into F-WO3-x structures and deactivates the polaron-IR coupling (IR transmission change from 20 to 70%) since all the band-edge defect states are passivated upon F insertion with a strong n-doping effect. Therefore, this approach, entirely processed at room temperature, is highly applicable to fluorine detecting sensors and devices utilizing the polaron-IR coupling effect.